2003
DOI: 10.2527/2003.81102546x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of corn intrinsic and recombinant DNA fragments and Cry1Ab protein in the gastrointestinal contents of pigs fed genetically modified corn Bt11 1

Abstract: Genetically modified corn has been approved as an animal feed in several countries, but information about the fate of genetically modified DNA and protein in vivo is insufficient. Genetically modified corn Bt11 is developed by inserting a recombinant DNA sequence encoding insecticidal Cry1Ab protein from Bacillus thuringiensis subsp. kurstaki. We examined the presence of corn intrinsic and recombinant cry1Ab gene by PCR, and the Cry1Ab protein by immunological tests in the gastrointestinal contents of five gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
74
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 15 publications
17
74
3
Order By: Relevance
“…Although few have found recombinant DNA sequences in any organ or tissue sample from animals fed GM plants (EFSA, 2007), our results showed that small DNA fragments can also be detected in kids organs when mothers are fed GM soybean. Recombinant plant DNA has also been found by other authors as a rare event (Chowdhury et al, 2003a;Mazza et al, 2005;Sharma et al, 2006) in organs and tissues of animals fed GM feeds. On the contrary, studies aiming at verifying the presence of transgenic fragments in milk gave negative results.…”
Section: R E T R a C T E Dmentioning
confidence: 61%
“…Although few have found recombinant DNA sequences in any organ or tissue sample from animals fed GM plants (EFSA, 2007), our results showed that small DNA fragments can also be detected in kids organs when mothers are fed GM soybean. Recombinant plant DNA has also been found by other authors as a rare event (Chowdhury et al, 2003a;Mazza et al, 2005;Sharma et al, 2006) in organs and tissues of animals fed GM feeds. On the contrary, studies aiming at verifying the presence of transgenic fragments in milk gave negative results.…”
Section: R E T R a C T E Dmentioning
confidence: 61%
“…Several studies have found no detrimental effects of feeding GM maize on the growth of pigs (Reuter et al, 2002;Chowdhury et al, 2003;Custodio et al, 2006;Flachowsky et al, 2007), poultry (Brake et al, 2003;Aeschbacher et al, 2005) or ruminants (Aumaitre et al, 2002;Trabalza-Marinucci et al, 2008). Higher feed intake and a tendency for higher kidney weight were observed in weanling pigs after 30 days of feeding GM maize (Walsh et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…None were detected in the liver, spleen, or lymph nodes indicating that they were too large to be systematically absorbed from the GI tract (Chowdhury et al 2003). It was suggested that transgenic nucleic acid and proteins from GM crops are handled in the gut like their conventional counterparts, with no evidence for systemic absorption of intact proteins or genes (Sieradzki et al 2013).…”
Section: World Controversymentioning
confidence: 99%